Associated production of single top quark and W boson through anomalous couplings at LHeC based γp colliders - Cakir, I. T.; Senol, A.; Tasci, A. T. (World Scientific Pub Co Pte Lt, 2014)
We consider the production of a single top quark in association with a W boson at LHeC based γp collider. We compute the cross-section for the process γp→WtX with the anomalous Wtb and Wtbγ couplings. We find that the sensitivities to anomalous couplings of top quark are shown to be comparable, even better than the ones obtained from direct searches at hadron colliders.
Keywords: High Energy Physics - Phenomenology; High Energy Physics - Phenomenology (hep-ph); FOS: Physical sciences